The Fence - Laura Malacart (European Journal of Life Writing)
‘The Fence’ weaves a critical reading of the author’s unusual first day in the UK in 1987 with a reflection on borders and discrimination applied to both humans and birds. The contingency and instability of borders create a relative and precarious status when it comes to human and nonhuman animals; this shifting position is subject to socio-economics, history, legislation and the politics of representation that contribute to the production of othering. Alongside societal contingencies, this work emphasises the role of individual agency which can affect and override the outcomes predicated by these structural limitations.